2019
DOI: 10.13164/re.2019.0320
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Synchronization-free TDOA Localization System Based on UWB

Abstract: At present, indoor localization system based on ultra-wideband (UWB) has attracted more and more attention. In UWB system, Time Difference of Arrival (TDOA) and Two-Way Ranging (TWR) are widely used. However, TDOA requires high-accuracy time synchronization between all anchor nodes and even slight noise can cause large localization error. In TWR, although two-way communication between anchor nodes with known location and blind nodes to be located can avoid the time synchronization issue effectively, the cloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…UWB also has a relation with the term ranging and ranging techniques, namely AoA and TDoA. This was stated by several papers that researched to increase positioning accuracy by carrying out various engineering techniques on TDoA [41], [42], [43], [44], [45] and AoA [46][47] based ranging techniques. Meanwhile, its connection with the term trilateration indicates a positioning method that has been proposed by many researchers to determine the position of a tag using 3 anchors [48].…”
Section: A the Sms Results Of Rq1 Rq2 And Rq3: Trend Bibliometric And...mentioning
confidence: 99%
“…UWB also has a relation with the term ranging and ranging techniques, namely AoA and TDoA. This was stated by several papers that researched to increase positioning accuracy by carrying out various engineering techniques on TDoA [41], [42], [43], [44], [45] and AoA [46][47] based ranging techniques. Meanwhile, its connection with the term trilateration indicates a positioning method that has been proposed by many researchers to determine the position of a tag using 3 anchors [48].…”
Section: A the Sms Results Of Rq1 Rq2 And Rq3: Trend Bibliometric And...mentioning
confidence: 99%
“…is problem can be improved by some speci c algorithms for tracking maneuvering targets, such as the Singer algorithm, Interactive Multi-Model algorithm, and so on. System Algorithm Accuracy (cm) Ubisense [22] AOA, TDOA 15-20 Zebra [23] TDOA 30 Sewio [24] TDOA 30-50 Asynchronous [25] TDOA 15.2 Sync-free [26] TDOA 20.4 is article TWR-TDOA-KF 10…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The synchronization-free methods, such as Sequential TDoA (S-TDoA) [17] rely on quick retranslation of the messages by the anchors; consequently, the positioning accuracy is severely limited by the retranslation delay and the clock performance. The research reported in [18] is claimed to be synchronization-free. However, the authors use Kalman filtering for estimation of the clock drift.…”
Section: Introductionmentioning
confidence: 99%